The emergence and development of Saussurean linguistic thought and structural linguistics in Turkey - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
The aim of this study is to analyse the emergence and development of Saussurean linguistic thought and structural linguistics in Turkey after the 1920s. Although Saussurean and structural linguistic studies can be traced back to the early stages of Turkey, most of these studies flourished after the 1960s. For example, Cours de Linguistique Ge ne rale was translated for the first time in 1976. This study has demonstrated that Saussurean linguistic thought and structural linguistics attracted prominent Turkish linguists' attention. However, probably due to the ideological and nationalistic concerns, conducting a better translation and forming a native linguistic terminology overshadow other linguistic contributions, although Turkish linguists conducted significant works in linguistics.
Keywords: Saussurean linguistic thought; structural linguistics; turkish linguists; linguistic developments in Turkey; nationalism and ideology; NATIONALISM